Antarctic Fish as a Global Pollution Sensor: Metals Biomonitoring in a Twelve-Year Period - Marrone, Alessandro; La Russa, Daniele; Brunelli, Elvira; Santovito, Gianfranco; La Russa, Mauro Francesco; Barca, Donatella; Pellegrino, Daniela (Frontiers in Molecular Biosciences, 2021)
Antarctica represents a unique natural laboratory for ecotoxicological studies as it is characterized by low internal pollutants emissions but high external contamination levels. Indeed, warm temperatures promote pollutant evaporation (low latitudes), while cool temperatures (high latitudes) promote its deposition from the atmosphere on land/water. Metals are the most important pollutants in ecosystems and represent a serious and global threat to aquatic and terrestrial organisms. Since 2000, the risks posed by metals have led many States to ratify protocols aimed at reducing their emissions. Endemic Antarctic organisms represent excellent bioindicators in order to evaluate the efficacy of global measures adopted to mitigate pollutants release into the environment. In this study (supported by PNRA18-00133), we estimated the metals contamination levels and the metallothionein-1 expression in liver samples of two Antarctic fish species, the icefish Chionodraco hamatus and the red-blooded Trematomus bernacchii, collected in the same area during 2002 and 2014. The chosen area is located in the Ross Sea, a unique area as it is also isolated from the rest of the Southern Ocean. The analysis of contamination trends throughout this period showed, in both species, a significant increase over time of metals bioaccumulation and metallothionein-1 expression. In addition, our result clearly indicated that the detoxifying ability of the two organisms analyzed greatly differs, probably due to haemoglobin presence/absence. Our work represents an important early step to obtain valuable information in conservation strategies for both Antarctic and non-Antarctic ecosystems.